A Practical Manual of Diabetic Retinopathy Management - Scanlon, P; Wilkinson, C; Aldington, S; Matthews, DR (Wiley-Blackwell, 2009)
Another title in the award winning 'Practical Manual' series from Wiley-Blackwell, following on from Edmonds, Foster and Sanders' APractical Manual of Diabetic Foot Care - winner of the British Medical Association's Medical Book of the Year Award 2004. This practical clinical manual covers the diagnosis, treatment and long-term management of eye problems in people with diabetes, with a strong emphasis on the importance of early diagnosis. Edited and authored by world-renowned experts from leading centres, APractical Manual of Diabetic Retinopathy Management presents evidence-based guidance relevant for a global audience. High quality photographs uniquely illustrate the lesions that occur in diabetic retinopathy and diagrams show the surgical techniques involved in vitreoretinal surgery for advanced stages of the disease Numerous real life case histories demonstrate the scenarios that one is likely to come across in a clinic treating patients with diabetic retinopathy The best colour guide to the spectrum of changes that occur in diabetic retinopathy This bookis a richly illustrated manual on the management of all stages of diabetic retinopathy, ideal for diabetologists, general endocrinologists who see patients with diabetes, retinal screeners, ophthalmologists and any other healthcare professionals involved in the care and management of diabetes. © 2009 Peter H. Scanlon, Charles P. Wilkinson, Stephen J. Aldington and David R. Matthews.